Sustainable shipping management: definitions, critical success factors, drivers and performance - Chua, Jie Ying (2023)
Sustainable shipping management (SSM) is one of the greatest challenges in the 21st century which attracts much attention and interest from global regulatory bodies, industry players, and academics. The objective of this study is to review and consolidate the topic of SSM, specifically, the definitions, critical success factors (CSFs), drivers, and their effects on organizational performance. A systematic review of academic journals is conducted. The review suggests that (1) there are seven CSFs of SSM, namely, government support, organizational commitment, strategic alignment, relationship management, knowledge management, technology acceptance, and performance measurement; (2) shipping firms are motivated to adopt SSM due to institutional pressure and the desire to enhance organizational performance; (3) SSM can lead to better financial and non-financial performances but the relationships are contingent on external and internal conditions. External conditions consist of the stakeholder influence capacity and shippers' belief whereas internal conditions involve the firms’ competitive strategy, continuous improvement capability, green capability, innovation capability, pace, and consistency. This study contributes to the literature by consolidating the scattered research on SSM, providing greater theoretical insight into the CSFs of SSM, the drivers of SSM, the impact SSM has on performances and implications to academia, government and policymakers, and strategic team of shipping companies to manage sustainability in the maritime transport industry.